Review on Different Marketing Strategies of Pharmacy Companies on Customers for Ahmednagar District: A Study on the Effectiveness of Marketing Strategies for Pharmacy Companies in Ahmednagar District (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper is dedicated to the identification of the published and unpublished work done by the other researchers in the area of pharmaceutical product poisoning through secondary data. The wastage of resources by reinventing the wheel has been reduced through literature review. It has given the fundamental framework of the study and helped to write the statement of the problem clearly and precisely. Inclusions of the important variables of the topic of the study and framing of the hypotheses, which are going to be tested, were identified through the literature review. It ensured stating a problem statement with clarity and precision which is required for enhanced reliability and testability of the findings of the current research.